ICU dan Non-ICU MRSA: Kejadian dan Faktor Risiko di Rumah Sakit Tersier - Tarigan, Junita; Putri, Maulinda; Suhartomi, Suhartomi; Sitompul, Owen (Nommensen Journal of Medicine, 2025)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a major nosocomial pathogen that is resistant to penicillin-class antibiotics and poses a serious threat to healthcare facilities. Its global prevalence reached 30% in 2020, while in Indonesia it ranges from 0.3% to 52%, with the highest rate reported in Jakarta. Objective: To compare the incidence and risk factors of MRSA among patients in the Intensive Care Unit (ICU) and general wards (non-ICU) at RSUP Haji Adam Malik Medan, during 2022–202. Methods: A cross-sectional study was performed on 569 patients in ICU and non-ICU wards with culture examinations performed from January 2022 to December 2023. Bivariate analysis was conducted for nine independent variables, followed by multivariate logistic regression for variables with p-values < 0.25. Results: From 18,121 culture examinations, 569 isolates of Staphylococcus aureus were identified. MRSA incidence was higher in non-ICU wards (246 of 441 isolates; 55.7%) than in the ICU (63 of 128 isolates; 49.2%). Statistically significant risk factors differed between the two groups: in ICU patients, only diabetes mellitus (OR 2.50; p = 0.017) was significant; while in non-ICU patients, chronic kidney disease (OR 0.644; p = 0.037) and a history of prior antibiotic use (OR 3.037; p = 0.011) were significant factors. Additionally, 4.21% of all isolates were confirmed as VRSA. Conclusion: MRSA incidence was higher among patients in non-ICU wards. The main risk factors differed between units: diabetes mellitus was prominent among ICU patients, whereas chronic kidney disease and previous antibiotic use played a role among non-ICU patients. These differences highlight the need for infection prevention and control strategies tailored to the specific risk profiles of each care unit.